Vaccinated Mice Remain More Susceptible to Mycobacterium tuberculosis Infection Initiated via the Respiratory Route than via the Intravenous Route - North, Robert J. (American Society for Microbiology, 1999)
Mice given Mycobacterium tuberculosis bacilli via the respiratory route succumbed much sooner to infection than mice given 1,000 times more bacilli via the intravenous route. Vaccination provided increased protection to an M. tuberculosis challenge infection; however, mice infected via the respiratory route remained much more susceptible.